Women labour migrant returnees and their changing roles in Nepal - Shree, Bisista (NUTA Journal, 2022)
This paper examines how the women foreign labour migrant looking at shifts in gender roles after returning to the home from the standpoint of family structure, public roles and factors to bring changes. It also explores how returnee women are perceived in society. Chautara and Duwachaur villages of Sindhupalchowk district were selected as the studied area. Data were collected fromforty female who have returned from foreign labor. Informations were collected from household survey, Interviews and Key informant Interview methords. Drastically change in the means of communication and its accessibility, higher level of income and economic empowerment are the key for shifting in gender role. It has not been a drastic difference between women roles after returning from abroad. Thus, family structure and ethnicity of the migrant family are key determinant factors for the changing role. In nuclear family gender roles was seen a significant change in comparison to joint families. Women of ethnic groups enjoy relatively more social freedom compared to women of higher-caste groups such as Brahmins and Chhetri. The major challenge for returnee women migration is the image of creating female workers as “victims’’ and deeply rooted in the socio-economic structures of Nepal.